A Case of COVID-19 Vaccine Associated New Diagnosis Myasthenia Gravis - Augustine Chavez; Charlotte Pougnier (SAGE Publishing, 2021)
An 82-year-old man presented with intermittent episodes of slurred speech during his evening meals after receiving the BNT162b2 COVID-19 vaccine. Thorough evaluation was conducted including lab work and EMG confirming a new diagnosis of late-onset myasthenia gravis. Despite treatment, the patient progressed rapidly to severe exacerbation requiring intubation and placement of a PEG tube. Infections provoking new diagnosis and exacerbations of myasthenia gravis have been reported. New diagnosis of myasthenia gravis associated with the COVID-19 vaccine is rarely reported. This case highlights the need for clinicians to be aware of the uncommon presenting symptoms in late-onset myasthenia gravis and the possibility of vaccine provoked diagnoses of immune mediated diseases.